2022
DOI: 10.1177/15593258221108280
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Studies Calculated a New Chitin Oligomer Binding Site Inside Vicilin: A Potent Antifungal and Insecticidal Agent

Abstract: Vicilins are major seed storage proteins and show differential binding affinities toward sugar moieties of fungal cell wall and insect gut epithelium. Hence, purpose of study is the thorough in-silico characterization of interactions between vicilin and chitin oligomer followed by fungal and insecticidal bioassays. This work covers the molecular simulation studies explaining the interactions between Pisum sativum vicilin ( PsV) and chitin oligomer followed by protein bioassay against different pathogens. LC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Not surprisingly, this fraction is associated with the vicilin family as mentioned by several authors (Saeed et al, 2022;Salgado et al, 2002). Other studies have also implicated vicilin as a protein that protects the cowpea seed against the damaging effect of the cowpea C. maculatus (Kpoviessi et al, 2021;Miranda et al, 2020;Rangel et al, 2003;Saeed et al, 2022). We infer that the presence of this protein plays a crucial role in C. maculatus tolerance in cowpea.…”
Section: Analysis Of Seed Storage Proteins and Seed Coat Compounds Th...supporting
confidence: 70%
See 1 more Smart Citation
“…Not surprisingly, this fraction is associated with the vicilin family as mentioned by several authors (Saeed et al, 2022;Salgado et al, 2002). Other studies have also implicated vicilin as a protein that protects the cowpea seed against the damaging effect of the cowpea C. maculatus (Kpoviessi et al, 2021;Miranda et al, 2020;Rangel et al, 2003;Saeed et al, 2022). We infer that the presence of this protein plays a crucial role in C. maculatus tolerance in cowpea.…”
Section: Analysis Of Seed Storage Proteins and Seed Coat Compounds Th...supporting
confidence: 70%
“…In the current study, only a 51 kDa fraction was observed to be associated with two C. maculatus tolerance measures, PAE and H.S.I., whereas other fractions were associated with one measure or the other singly. Not surprisingly, this fraction is associated with the vicilin family as mentioned by several authors (Saeed et al, 2022;Salgado et al, 2002). Other studies have also implicated vicilin as a protein that protects the cowpea seed against the damaging effect of the cowpea C. maculatus (Kpoviessi et al, 2021;Miranda et al, 2020;Rangel et al, 2003;Saeed et al, 2022).…”
Section: Analysis Of Seed Storage Proteins and Seed Coat Compounds Th...mentioning
confidence: 81%